Temperature Control for Seaweed Dryer Based on PID - mukti, krisna (Universitas Muhammadiyah Surakarta, 2024)
Seaweed is a commodity that has great potential in terms of establishing small or medium scale community businesses which are usually referred to as SMEs. The first thing you need to know about cultivating seaweed is the drying process, which aims to reduce the water content of the seaweed. When drying seaweed, people still use the traditional method, namely drying it in the sun, which takes 2 to 3 days. During the rainy season, farmers have to take 3 to 5 days for good results. Apart from that, the work is still manual or traditional, namely drying seaweed which takes quite a long time. If the weather when harvesting seaweed is rainy season, it will cause losses to seaweed farmers. As an alternative, a PID-based seaweed temperature and humidity control device has been developed using a light bulb heater as a substitute for sunlight for the process of drying the seaweed. The DS18B20 sensor is used to measure temperature, which is then displayed on the LCD. The Arduino Uno microcontroller is used to control the seaweed drying tool. This seaweed dryer can speed up drying by utilizing the Arduino system to reduce humidity so that drying time is faster. The results obtained with this simple seaweed dryer can speed up the drying process to 1.5 to a maximum of 2 days and the quality of the dried seaweed is better because it is protected from surrounding dust and dirt. The result of this research is a seaweed dryer that can help farmers dry the results of their seaweed cultivation in any weather conditions with the hope of better results.